A narrative commentary about interoperability in medical devices and data used in diabetes therapy from an academic EU/UK/US perspective - Jendle, Johan; Adolfsson, Peter; Choudhary, Pratik; Dovc, Klemen; Fleming, Alexander; Klonoff, David C; Mader, Julia K; Oliver, Nick; Sherr, Jennifer L; Šoupal, Jan; Heinemann, Lutz (Diabetologia (Berlin), 2024)
People living with diabetes have many medical devices available to assist with disease management. A critical aspect that must be considered is how systems for continuous glucose monitoring and insulin pumps communicate with each other and how the data generated by these devices can be downloaded, integrated, presented and used. Not only is interoperability associated with practical challenges, but also devices must adhere to all aspects of regulatory and legal frameworks. Key issues around interoperability in terms of data ownership, privacy and the limitations of interoperability include where the responsibility/liability for device and data interoperability lies and the need for standard data-sharing protocols to allow the seamless integration of data from different sources. There is a need for standardised protocols for the open and transparent handling of data and secure integration of data into electronic health records. Here, we discuss the current status of interoperability in medical devices and data used in diabetes therapy, as well as regulatory and legal issues surrounding both device and data interoperability, focusing on Europe (including the UK) and the USA. We also discuss a potential future landscape in which a clear and transparent framework for interoperability and data handling also fulfils the needs of people living with diabetes and healthcare professionals.
Keywords: United Kingdom; Diabetes Mellitus; Blood Glucose Self-Monitoring; krevní glukóza; Spojené království; Humans; diabetes mellitus; lidé; Blood Glucose; selfmonitoring glykemie; Electronic Health Records; elektronické zdravotní záznamy